The Needs of the Many and the Needs of the Few: A New System of Public Interest Intervention for New Zealand - Clark, Edward (Victoria University of Wellington Law Review, 2005)
The traditional adversarial system sees the courts as simply a means of resolving disputes between private parties. The dispute is thus no one else’s concern but the parties’. This view of the courts’ role, however, fails to take into account judicial lawmaking. If a person is affected by an act of lawmaking, it is only just that they should have a chance to be heard. Further, before they make a decision the courts should understand the perspectives of those who will be affected by the rule laid down. This article argues that allowing affected nonparties to make submissions as public interest intervenors will assist both the affected persons and the courts. In order to balance the interests of the parties, the intervenors, and the public at large effectively, a comprehensive system of rules that both welcome and regulate public interest intervention is needed. This article recommends the adoption of such a system of rules, substantially based on the effective and well established rules on intervention contained in the Rules of the Supreme Court of Canada.